2003
DOI: 10.1016/s0886-3350(03)00058-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective and specific targeting of lens epithelial cells during cataract surgery using sealed- capsule irrigation

Abstract: We describe the technique of sealed capsule irrigation, which aims to reduce posterior capsule opacification and better control lens epithelial cell activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 6 publications
0
46
0
2
Order By: Relevance
“…A recent Cochrane review [22] of 53 studies looking at interventions for preventing PCO found that sharp-edged IOLs gave a significantly lower PCO score and YAG (yttrium aluminium garnet) laser rate than roundedged IOLs. It is conceivable that IOLs will be designed that can deliver slow release molecules to reduce inflammation (dexamethasone-coated IOL reduced post-operative inflammation in rabbit eyes) [23] or PCO rate, or devices such as the Perfect Capsule [24], irrigated with antimitotic agents such as 5-fluorouracil, will be used to prevent PCO (shown to be successful in young rabbit eyes) [25].…”
Section: Clinical Aspects Of Congenital or Paediatric Cataract (A) Comentioning
confidence: 99%
“…A recent Cochrane review [22] of 53 studies looking at interventions for preventing PCO found that sharp-edged IOLs gave a significantly lower PCO score and YAG (yttrium aluminium garnet) laser rate than roundedged IOLs. It is conceivable that IOLs will be designed that can deliver slow release molecules to reduce inflammation (dexamethasone-coated IOL reduced post-operative inflammation in rabbit eyes) [23] or PCO rate, or devices such as the Perfect Capsule [24], irrigated with antimitotic agents such as 5-fluorouracil, will be used to prevent PCO (shown to be successful in young rabbit eyes) [25].…”
Section: Clinical Aspects Of Congenital or Paediatric Cataract (A) Comentioning
confidence: 99%
“…48 To be used routinely in human subjects, toxic effects on neighbouring tissues would need to be avoided and sealed capsule irrigation has been suggested for safe application of pharmaceutical agents. 138,139 In conclusion, numerous challenges need to be addressed successfully to restore accommodative function to the presbyopic eye. The ultimate goal of restoring eye focus to youthful levels is yet to be achieved and much further work is necessary before such a treatment becomes available for human use.…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth was measured daily using the 3-(4,5-dimethythiazl-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)2H-tetrazolium inner salt (MTT) test. 32 …”
Section: Immunoblottingmentioning
confidence: 99%
“…Apoptosis was evaluated quantitatively by measuring phosphatidylserine externalization, an early apoptotic alteration. 32 This was performed by fluorescence staining using the annexin V-FLUO staining kit (Roche, France) as per the manufacturer's recommendations. The proportion of annexin V-stained cells was determined.…”
Section: Analysis Of Apoptosismentioning
confidence: 99%